Application of zakat accounting standards, transparency and internal control systems on the BAZNAS accountability - Yusiresita Pajaria; Hurian Kamela (Institute of Computer Science (IOCS), 2024)
This research aims to determine the effect of implementing zakat accounting standards, transparency and internal control systems on financial accountability. The samples used in this research were employees of the Banyuasin and Musi Banyuasin Amil Zakat Agency. The research population consisted of 30 people. The research sample consisted of 30 people and the sampling technique used non-probability sampling technique with saturated sampling technique. The data analysis technique uses multiple linear regression. Partial research results (t test) show that the variables of zakat accounting standards, transparency and the Internal Control System have an effect on financial accountability. Simultaneous results (f test) show that zakat accounting standards, transparency, internal control systems have a significant effect on financial accountability. The results of the coefficient of determination (R2) show that 59.4% of the variables of zakat accounting standards, transparency and internal control systems have an influence on financial accountability while the rest are influenced by other variables not measured in this research.